Multivariate Regression Compared with Moving Average Smoothing - Asuming, Emmanuel (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Regression analysis is a statistical method having application in all fields of scientific and technological studies. Theoretical concepts lead to the development of regression theory are examined in some detail to lay down the foundation for the application of the theory. In statistics regression is mainly used to establish the kind of relationship between dependent and independent variables, i.e. linear or any other type. Moving average is a statistical method widely used for smoothing out raw data trajectories to obtain trends by filtering out the noise from the random fluctuations. The trend is an estimation of the functional behavior of the variable under study. This thesis is first centered on the theoretical characteristics of linear regression in chapter 3, examining the abstract concepts behind the regression theory, and the least squares method for establishing the model to be fitted from available data. Chapter 4 is allocated for the moving average technique used as a smoother of the trajectory for a variable. That smooth trend can be generated for every variable. The fitted regression model itself can be considered a smooth functional representation of the response variable in relation to the predictor/s. In Chapter 5 a case study of a data set is undertaken, where moving average technique was implemented for smoothing with 2 different orders, using m = 3 and m = 6 values for averaging of a real life data. It became evident that the smoother the data, the lower the error measures will be in a regression analysis. However, too much smoothing of a variable will runs the risk of obtaining close to a perfect regression fit, which will not be realistic. Based on the results obtained in the case study, it was then recommended that where large data sets are used for regression study, some smoothing can be beneficial as it will result in reduced estimation errors. Some software programs like Excel, Minitab, and S.P.S.S were all used to help in data processing to find the needed outputs.

ÖZ: İstatistiksel bir metod olan regresyon analizi bilim ve teknolojinin her alanında kullanılabiliyor. Regresyon teorisinin geliştirilmesinde kullanılan kavramların uygulanabilmesi için gerekli altyapıyı oluşturmak açısından detaylı bir şekilde incelenmiştir. İstatistikte regresyon bağımlı ve bağımsız değişkenler arasındki ilişkiyi tayin etmede kullanılıyor. Hareketli ortalama yöntemi bir değişkene ait ham verilerin grafiğindeki aşırı dalgalamaları azaltma veya düzgünleştirme amaçlı kullanılıyor. Bir bakıma şansa bağlı aşırı dalgalanmaları filtre ediyor. Elde edilen düzgünleştirilmiş grafik değişkenin fonksiyonel hareketinin bir tahminisi olarak da düşünülebilir. Bu tezde lineer regresyonun teorik karakteristikleri Kısım 3 de ele alınmıştır. Regresyon teorisinin temelini oluşturan bazı soyut kavramlar, ve veriden oluşturulacak regresyon modelinin belirlenmesinde elzem olan en küçük kareler metodu incelenmiştir. Kısım 4 hareketli ortalamar metodunun incelenmesine ayrılmıştır. Her değişken için düzgünleştirilmiş grafiğin nasıl üretilebileceği anlatılmıştır. Veriden elde edilen regresyon grafiği, bağımlı değişkenin bağımsız değişken/lere olan ilişkisinin fonksiyonel bir temsiliyetidir. Kısım 5de yapılan uygulamada hareketkli ortalama metodu ile m = 3 ve m = 6 değerleri kullanılarak gerçek hayattan alınmış verilerin düzgünleştirilmesi yapılmıştır. Ham ve düzgünleştirilmiş veriler kullanılarak yapılan regresyon analizlerinden de görülmüştür ki düzgünleştirme arttıkca, regresyonda ortaya çıkan hata payları azalmıştır. Ancak aşırı düzgünleştirmenin regresyon hatalarını sıfıra doğru indireeği düşünülürse, greçekci olmadığı ortadadır. Uygulamadan elde edilen sonuçlara bakarak büyük verilerin elde olduğu durumlarda bir miktar düzgünleştirmenin hata payların azaltmak açısından faydalı olacağı ortadadır. Bu çalışmada Excel, Minitab, ve SPSS gibi istatistik paket yazılımlardan fadalanılmıştır.
Master of Science in Applied Mathematics and Computer Science. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2021. Supervisor: Asst. Prof. Dr. Yücel Tandoğdu.
Keywords: Mathematics Department; Applied Mathematics and Computer Science; Principal components analysis; Matrix algebra, regression analysis, estimation, predictors, response, regression coefficient, moving average, stretched interpolated moving average